Factor Proportions and the Structure of American Trade: Further Theoretical and Empirical Analysis: Comment - Leontief, Wassily W. (The Review of Economics and Statistics, 1958)
Wassily W. Leontief, Factor Proportions and the Structure of American Trade: Further Theoretical and Empirical Analysis: Comment, The Review of Economics and Statistics, Vol. 40, No. 1, Part 2. Problems in International Economics (Feb., 1958), pp. 111-116